Generation Z and the MUI Fatwa: What Shapes the Boycott of Israeli Products? - Jannati, Agitsna; Sahal, Lutpi; Hidayat, Muhammad Rifqi; Mumtazah, Fitria (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the factors that influence Generation Z’s (Gen Z) perception of Indonesian Ulema Council (MUI) Fatwa No. 83 of 2023 regarding the boycott of products affiliated with Israel. Although many Gen Z individuals support the boycott verbally, in reality, many do not implement it through concrete actions. This study employs a field research method with a qualitative descriptive approach. Data collection techniques include interviews and observations. Based on the Theory of Planned Behavior (TPB), this study identifies three main factors that influence Gen Z’s perception: attitudes toward behavior, subjective norms, and perceived behavioral control. A positive attitude toward the boycott, driven by religious beliefs and humanitarian solidarity, is the primary factor in supporting the fatwa. Subjective norms, particularly the influence of social environments such as family, friends, and religious leaders, also shapes the intention to act. However, obstacles such as difficulties in changing consumption habits and doubts about the effectiveness of the fatwa serve as barriers for some Gen Z individuals in joining the boycott. This study provides additional understanding into the behavioral dynamics of Gen Z regarding the boycott fatwa and highlights the importance of a direct approach in increasing support for this fatwa.